The notary's moral responsibility to provide legal counseling to the parties in making the sale and purchase deed - Munjayanah Dwi Harviah; Irwan Santosa; Iskandar Muda (SEAN Institute, 2024)
Notary is a general official who is authorized to make authentic deeds and has other authorities. Notary authority in providing legal counseling based on the law of the notary position, a notary must educate the public or the parties and be morally responsible to the parties in making the sale and purchase deed, which will make the deed before the notary regarding rights and obligations. According to the applicable provisions, the sale and purchase of land rights must be carried out before the PPAT, but in everyday life it turns out that there are still many transfers of land rights carried out under the hands in the sense that they are not carried out in accordance with applicable regulations, this will certainly be very detrimental to the buyer, because he can only control the right to land physically, legally ownership of the land is fixed with the seller. This research uses a normative juridical approach method, The data used are secondary data, Data analysis used normative analysis, The purpose of this study is to determine the moral responsibility of notaries in providing legal counseling to the parties. As well as legal consequences for notaries who do not provide legal counseling to the parties in making the sale and purchase deed. The results of this study show that the sale and purchase of land carried out by a receipt is legal as long as the material conditions are met. Efforts can be made to buy and sell land with a receipt by filing a lawsuit with the chairman of the competent local district court.